Qualitative Research in English Language Teaching and Learning - Jixian Wang (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2018)
This paper presents the theoretical framework and features of qualitative research, as well as its approaches, data collection and data analysis, advantages and disadvantages. The statistics show that qualitative research method has dramatically risen in popularity over the last fifteen years. It includes discussion on the contribution of qualitative research in terms of both its popularity and suitability to the field of English language teaching and learning. The specifics for how qualitative research is implemented in the field of language learning and teaching will be specifically explored. Two articles will be reviewed in terms of their application of qualitative research method. This will be done in order to provide insights for literature reviews conducting qualitative studies in the research relevant to the interests of this essay.This research enriches the literature of qualitative research in the field of English language teaching and learning.